Impact of Dietary Phytochemicals on Gut Microbiota and Intestinal Barrier Integrity – Nutritional Interventions and Their Role in Chronic Diseases Prevention - Michalak, Klaudia; Janowski, Kacper; Piotrowicz, Emilia; Góras, Sandra (Quality in Sport, 2025)
Introduction: In recent decades, the development of chronic diseases has become a global problem burdening health care resources. The intestinal microbiota is a complex community of microbes involved in maintaining host homeostasis, and nutritional interventions affecting its functioning are the subject of many scientific studies. Phytochemicals are bioactive components of plants that have multiple actions in the metabolic pathways of human cells. There are many studies describing their diverse activities, including anti-inflammatory, anti-cancer, anti-allergic, and antioxidant. In this review, we described the effects of resveratrol, quercetin, curcumin, fisetin, berberine on the gut microbiota and intestinal barrier integrity through various metabolic pathways and the effects of their consumption on the development of chronic diseases. Materials and Methods: The analysis was conducted based on data available in studies found in the PubMed database. The research concerned the impact of phytochemicals on the gut microbiota and intestinal barrier integrity and their relationship with the development of chronic diseases. Conclusions: Studies indicate that diet has a direct impact on the state of the gut microbiota. A link between the consumption of products rich in phytochemicals and the reduction of the development of chronic diseases through the modulation of the gut microbiota has been described. Dietary interventions are an interesting and promising research subject, and development in this field should continue to be implemented in clinical practice.